Effects of stepped psychooncological care on referral to psychosocial services and emotional well‐being in cancer patients: A cluster‐randomized phase III trial. Issue 10 (20th July 2017) - Singer, Susanne; Danker, Helge; Roick, Julia; Einenkel, Jens; Briest, Susanne; Spieker, Henning; Dietz, Andreas; Hoffmann, Isabell; Papsdorf, Kirsten; Meixensberger, Jürgen; Mössner, Joachim; Schiefke, Franziska; et al.
Abstract: Objective: Emotional distress in cancer patients often goes unnoticed in daily routine; therefore, distress screening is now recommended in many national guidelines. However, screening alone does not necessarily translate into better well‐being. We examined whether stepped psychooncological care improves referral to consultation‐liaison (CL) services and improves well‐being. Methods: In a cluster‐randomized trial, wards were randomly allocated to stepped versus standard care. Stepped care comprised screening for distress, consultation between doctor and patient about the patient's need for CL services, and provision of CL service. Primary outcomes were referral to psychosocial services and emotional well‐being half a year after baseline, measured with the Hospital Anxiety and Depression Scale. A secondary endpoint was uptake of outpatient health care. Analysis employed mixed‐effects multivariate regression modeling. Results: Thirteen wards were randomized; 1012 patients participated. With stepped care ( N =  570; 7 wards), 22% of the patients were referred to CL services and 3% with standard care ( N =  442; 6 wards; odds ratio [OR] 10.0; P  < .001). Well‐being 6 months after baseline was 9.5 after stepped care ( N =  341) and 9.4 after standard care ( N =  234, β −0.3; P  = .71). After stepped care, patients with psychiatric comorbidity went more often to psychotherapists (OR 4.0, P  = .05) and to psychiatrists (OR 2.3, P  = .12), whereas patients without comorbidity used psychiatrists less often (OR 0.4, P  = .04) than in standard care. Conclusions: Stepped care resulted in better referral to CL services. The patients' emotional well‐being was not improved, but uptake of outpatient psychiatric help was increased in patients with psychiatric comorbidity and decreased in patients without.